Whence Consumer Loyalty? - Oliver, Richard L. (Journal of Marketing, 1999)
Both practitioners and academics understand that consumer loyalty and satisfaction are linked inextricably. They also understand that this relation is asymmetric. Although loyal consumers are most typically satisfied, satisfaction does not universally translate into loyalty. To explain the satisfaction–loyalty conundrum, the author investigates what aspect of the consumer satisfaction response has implications for loyalty and what portion of the loyalty response is due to this satisfaction component. The analysis concludes that satisfaction is a necessary step in loyalty formation but becomes less significant as loyalty begins to set through other mechanisms. These mechanisms, omitted from consideration in current models, include the roles of personal determinism (“fortitude”) and social bonding at the institutional and personal level. When these additional factors are brought into account, ultimate loyalty emerges as a combination of perceived product superiority, personal fortitude, social bonding, and their synergistic effects. As each fails to be attained or is unattainable by individual firms that serve consumer markets, the potential for loyalty erodes. A disquieting conclusion from this analysis is that loyalty cannot be achieved or pursued as a reasonable goal by many providers because of the nature of the product category or consumer disinterest. For some firms, satisfaction is the only feasible goal for which they should strive; thus, satisfaction remains a worthy pursuit among the consumer marketing community. The disparity between the pursuit of satisfaction versus loyalty, as well as the fundamental content of the loyalty response, poses several investigative directions for the next wave of postconsumption research.